2001
DOI: 10.1161/hh1201.093511
|View full text |Cite
|
Sign up to set email alerts
|

MinK-Related Peptide 1

Abstract: Abstract-The HCN family of ion channel subunits underlies the currents I f in heart and I h and I q in the nervous system.In the present study, we demonstrate that minK-related peptide 1 (MiRP1) is a ␤ subunit for the HCN family. As such, it enhances protein and current expression as well as accelerating the kinetics of activation. Because MiRP1 also functions as a ␤ subunit for the cardiac delayed rectifier I Kr , these results suggest that this peptide may have the unique role of regulating both the inward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(101 citation statements)
references
References 11 publications
7
93
1
Order By: Relevance
“…Third, each subunit controls expression and/or stability of the other in neurons where both are expressed. Although the mps-1 knockdown effects on KVS-1 expression are consistent with previous observations showing that mammalian MiRPs alter protein expression levels of some pore-forming subunits (4,14,33), kvs-1 RNAi effect on MPS-1 protein levels is a novel observation suggesting that neither subunit is dispensable in physiological cell types in which a complex is programmed to be assembled. Fourth, in CHO cells KVS-1 forms functional channels whose characteristics are markedly altered upon co-expression with MPS-1.…”
Section: Mps-1 Associates With Kvs-1 In a Subset Of Amphidsupporting
confidence: 90%
See 1 more Smart Citation
“…Third, each subunit controls expression and/or stability of the other in neurons where both are expressed. Although the mps-1 knockdown effects on KVS-1 expression are consistent with previous observations showing that mammalian MiRPs alter protein expression levels of some pore-forming subunits (4,14,33), kvs-1 RNAi effect on MPS-1 protein levels is a novel observation suggesting that neither subunit is dispensable in physiological cell types in which a complex is programmed to be assembled. Fourth, in CHO cells KVS-1 forms functional channels whose characteristics are markedly altered upon co-expression with MPS-1.…”
Section: Mps-1 Associates With Kvs-1 In a Subset Of Amphidsupporting
confidence: 90%
“…A well-established characteristic of MiRPs is the capacity to associate with multiple pore-forming subunits in heterologous systems. For instance, MiRP1 can associate with HERG, KCNQ1, HCN, and Kv4.2 subunits (2,(13)(14)(15). Indeed, MiRP "promiscuity" has considerable biomedical implications, because, if a single MiRP coassembles with multiple pore-forming subunits, genetic mutations would be predicted to lead to disruption of multiple currents simultaneously.…”
mentioning
confidence: 99%
“…The Kv:KCNE ion channel complexes are heterohexameric structures consisting of four a-subunits and two KCNE peptides [Morin and Kobertz, 2008]. The KCNE peptides modulate several potassium currents in the heart [Abbott and Goldstein, 2002;Abbott et al, 1999;Grunnet et al, 2003;Lewis et al, 2004;McCrossan et al, 2003;Yu et al, 2001;Zhang et al, 2001], including I Ks [Bendahhou et al, 2005], I Kr [Abbott and Goldstein, 2002], and possibly I to [Delpon et al, 2008]. The minK peptide, encoded by KCNE1, has been shown convincingly to confer a slow activation to the KCNQ1 channel, characteristic of the I Ks current, whereas the MiRP2:KCNQ1 complex is a constitutively active potassium channel [Schroeder et al, 2000].…”
Section: Brs6-mutations In Kcne3mentioning
confidence: 99%
“…Qualitative single-cell RT-mPCR experiments have shown that DA SN neurons coexpress three of the four I h channel subunits, HCN2, HCN3, and HCN4 (Franz et al, 2000). However, the molecular composition of native neuronal I h channels that might exist as homomeric or heteromeric complexes (Chen et al, 2001;Ulens and Tytgat, 2001;Yu et al, 2001) as well as the possible differential I h channel subunit expression between different DA subpopulations remains unclear. In this context, quantitative differences in HCN subunit expression might also play a significant role.…”
Section: Functional Diversity Of Anatomically and Neurochemically Idementioning
confidence: 99%